Estudo comparativo entre ressecção e eletrocoagulação endometrial em paciebtes com sangramento uterino anormal - Elias, Leonardo Vieira [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Purpose of the study. Compare the results of two techniques of endometrial ablation first generation. Type of study. Prospective, longitudinal and analytical study (Canadian Task Force II-2). The study site. Tertiary public hospital, university teaching center. Patients and methods. During the period October 2011 to September 2013, 73 patients with a history of abnormal uterine bleeding (AUB) and poor response to medical treatment for a minimum period of 12 months, were randomized and underwent endometrial ablation with monopolar resection electrode handle U followed by rollerball electrocoagulation with the group a (36 patients) with rollerball electrocoagulation only in group B (37 patients). The women were followed for an average period of 359 days (280;751) and 370 days (305;766), respectively. Interventions. The patients were submitted to endometrial ablation technique according to each group. Ratings at 30, 90, 180 and 360 days were accomplished through research protocol, which sought to assess the pattern of bleeding, associated symptoms, failure rate and satisfaction rate. Results. The groups were homogeneous clinical and epidemiologically (P ≥ 0.05). Surgical time and the volume of distension medium used were lower in group B patients [mean of 48.5 (±12.0) vs. 31.9 (±5.6) minutes; P < 0.001 and 5.700 mL vs. 3.500 mL; P < 0.01]. There was a significant improvement in clinical symptoms after endometrial ablation in both groups, reducing the number of bleeding days (P < 0.01), as well as the number of pads used on the day of the flow rate (P < 0.01) and throughout the menstrual cycle (P < 0.01). There was also a lower incidence of surgical site infection in group B (30.5% vs. 8.1%; P < 0.05). The hysterectomy rate observed in the study was 9.6%, due to technical difficulties and intraoperative hemorrhage, persistence of SUA, development of incapacitating dysmenorrhea and / or pelvic pain ...

Objetivo do estudo. Comparar os resultados entre duas técnicas de ablação endometrial de primeira geração. Tipo de estudo. Estudo prospectivo, longitudinal e analítico (Canadian Task Force II-2). Local do estudo. Hospital público terciário, centro universitário de ensino. Pacientes e métodos. Durante o período de outubro de 2011 a setembro de 2013, 73 pacientes com história de sangramento uterino anormal (SUA) e resposta insatisfatória ao tratamento clínico por um período mínimo de 12 meses, foram randomizadas e submetidas à ablação endometrial por ressecção com eletrodo monopolar em alça U seguida de eletrocoagulação com rollerball no grupo A (36 pacientes) e eletrocoagulação apenas com rollerball no grupo B (37 pacientes). As mulheres foram acompanhadas por período médio de 359 dias (280;751) e 370 dias (305;766), respectivamente. Intervenções. As pacientes foram submetidas à ablação endometrial conforme a técnica de cada grupo. Avaliações nos tempos 30, 90, 180 e 360 dias foram realizadas através de protocolo de pesquisa, que procurou avaliar o padrão de sangramento, sintomas associados, índice de falha e taxa de satisfação. Resultados. Os grupos foram clínico-epidemiologicamente homogêneos (P ≥ 0,05). O tempo cirúrgico e o volume utilizado do meio distensor foram menores nas pacientes do grupo B [média de 48,5 (±12,0) vs. 31,9 (±5,6) minutos; P < 0,001 e 5.700 mL vs. 3.500 mL; P < 0,01]. Observou-se uma considerável melhora no quadro clínico após ablação endometrial, em ambos os grupos, com redução do número de dias de sangramento (P < 0,01), assim como do número de absorventes utilizados no dia de maior fluxo (P < 0,01) e durante todo o período menstrual (P < 0,01). Houve também menor incidência de infecção do sítio cirúrgico no grupo B (30,5% vs. 8,1%; P < 0,05). A taxa de histerectomia observada no estudo foi de 9,6%, decorrente de ...
Comparative study of endometrial resection and eletrocoagulation in patients with abnormal uterine bleeding
Keywords: Técnicas ablação endometrial; Histeroscopia; Utero - Cirurgia; Hemorragia uterina; Satisfação do paciente; Estudo comparativo; Cirurgia - Tecnica; Hysteroscopy; Endometrial Ablation Techniques